Submandibulary Abscess With Molar Teeth Pulp Necrosis - Syifomade, Tania; Suseno, Setiawan; Rizal, Wahyu Tauhid Nur (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: A Submandibular abscess is an accumulation of pus in the submandibular region, often caused by odontogenic infections. An untreated submandibular abscess can lead to life-threatening complications. Case: A 47-year-old woman presented to the emergency department with progressive swelling of the left neck, dysphagia, and respiratory distress. She had a history of intermittent dental pain for two years. Examination revealed submandibular swelling extending to the neck, with erythema, warmth, tenderness, and fluctuance. Intraoral examination showed deep caries in tooth 37, residual root of tooth 46, and poor oral hygiene. Case Treatment: This case was managed collaboratively with the general surgery department, involving an extraoral incision and drainage, antibiotic therapy (ceftriaxone 2 x 1g IV and metronidazole 3 x 500mg IV), and tooth extraction to expedite recovery. Discussion: Dental plaque and debris containing carbohydrates are converted into lactic acid by bacteria, leading to tooth structure destruction. This creates a pathway for bacterial invasion of the apical region, infecting the cancellous bone and cortical bone. The infection can spread through the bone to the soft tissues. Anatomically, mandibular molar tooth infections can easily spread to the buccal space and submandibular space. Conclusion: Tooth extraction is crucial in managing submandibular abscesses with odontogenic infections to prevent recurrence.